The Use of Specific Non-Saccharomyces Yeasts as Sustainable Biocontrol Solutions Against Botrytis cinerea on Apples and Strawberries - Zukisani Gomomo; Morris Fanadzo; Maxwell Mewa-Ngongang; Boredi Silas Chidi; Justin Wallace Hoff; Marieta van der Rijst; Lucky Mokwena; Mathabatha Evodia Setati; Heinrich Wilbur du Plessis (Journal of Fungi)
Apples and strawberries hold significant commercial and nutritional value but face pre- and post-harvest spoilage due to infections by Botrytis cinerea. While spoilage is conventionally managed using synthetic chemicals, there is a growing interest in utilising yeasts as biological control agents. This study aimed to assess the antifungal potential of non-Saccharomyces yeasts Suhomyces pyralidae, Meyerozyma guilliermondii, Pichia kluyveri, Zygoascus hellenicus, and Aureobasidium melanogenum against three B. cinerea strains (B05.10, IWBT-FF1, and PPRI 30807) on agar plates and in post-harvest trials on apples and strawberries. Aureobasidium melanogenum exhibited a broad range of extracellular enzyme production and inhibition rates of 55%, 52%, and 40% against the strains. In volatile organic compound (VOC) assays, P. kluyveri and S. pyralidae achieved 79% and 56% inhibition, respectively, with VOCs like isobutanol, isoamyl alcohol, 2-phenylethanol, isoamyl acetate, and 2-phenethyl acetate identified. In post-harvest trials, S. pyralidae was most effective on apples, with inhibition rates up to of 64%. The commercial fungicide Captan and S. pyralidae and P. kluyveri achieved 100% inhibition against the B. cinerea strains B05.10 and IWBT-FF1 on strawberries. These findings highlight the potential of the selected yeast species as biological control agents against B. cinerea, warranting further research into their application in commercial fruit protection.